2020
DOI: 10.21608/niles.2020.165718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses ’Performance Regarding Care for Elderly Stroke Patients

Abstract: Background:Aging is a natural process of accumulation of diverse deleterious change occurring in cells and tissue with advancing age that are responsible for the increased risk of chronic disease as stroke. Aim: To assess nurses' performance regarding care for elderly stroke patients. Methods: a descriptive research design was performed on a convenient sample consisted of 68 nurses were available at four departments which are male neurological department, female neurological department, neurological care unit,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
3
1
0
Order By: Relevance
“…The findings of the study indicate that less than half) 41.67%( of nurses are between age's group between (25-29) years old. This results has also been found in a study by (Nagep, et al, 2020) which revealed that there was the most of nurses (85.3 %) within the age group (18 -< 30 years). Another studies conducted by Liao, et al, (2018) andBjartmarz, et al, (2018) who found that the high percent of the nurses were in the age group of less than 35 years old.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the study indicate that less than half) 41.67%( of nurses are between age's group between (25-29) years old. This results has also been found in a study by (Nagep, et al, 2020) which revealed that there was the most of nurses (85.3 %) within the age group (18 -< 30 years). Another studies conducted by Liao, et al, (2018) andBjartmarz, et al, (2018) who found that the high percent of the nurses were in the age group of less than 35 years old.…”
Section: Discussionsupporting
confidence: 84%
“…The findings of the study indicate that more than half of the study participants are in the age group(25 -29), which represents (53.3%) of nurses in the experimental group and (30%) of the control group. This result was also found in a study conducted byNagep et al (2020), who found that most nurses in both study and control groups were between the ages of 18 and 30 years old. Studies conducted byLiao, et al, (2018) andBjartmarz, et al, (2017) found that more than half of nurses were in the age group of less than 35 years old.…”
supporting
confidence: 84%
“…The study was carried out during the period from 1 st September 2021 to 1 st May 2022. A non-probability (purposive) sample consisted of (60) nurses, divided into two groups, (30) nurses in the study group were exposed to the nursing interventional program; (30) nurses who were not exposed to the program were considered in the control group and were randomly assigned to each one. The criteria for the selection of the study sample were: nurses who are working in the emergency department and neurological ward, both genders, with one year of service and more; nurses who are working in two shifts (morning and night).…”
Section: Methodsmentioning
confidence: 99%
“…contribute to lack of training courses that re ect on quality of patient care, job performance, care burden and care providers' quality of life. This nding matched with(Nagep, 2021) who conducted study about "Assessment of Nurses' Performance Regarding Care for Elderly Stroke Patients" and showed that less than half of the studied nurses haven't received any previous training courses.…”
supporting
confidence: 74%